Evaluation Of The U.S. Regulatory Process For Crops Developed Through Biotechnology - Chassy, Bruce M.; Abramson, Stanley H.; Bridges, Anne; Dyer, William E.; Faust, Marjorie A.; Harlander, Susan K.; Hefle, Susan L.; Munro, Ian C.; Rice, Marlin E. (Council for Agricultural Science and Technology (CAST), 2001)
A group of nine science and policy experts prepared this evaluation of the process by which U.S. regulatory agencies determine the safety of biotechnology-derived crops. The authors found that the U.S. regulatory process is comprehensive and meets its charge of ensuring that biotechnology-derived foods are at least as safe as foods derived using traditional breeding techniques. The paper poses and then answers questions about how safety assessments and regulatory reviews are conducted, what strengths and weaknesses can be identified in those reviews, and whether there are improvements in the regulatory process that would enhance public confidence in the process. The authors offer ten recommendations for policy and research in agricultural biotechnology.